Fortifikasi Zat Besi dari Hati Ayam pada Makanan Pendamping ASI - Risnawati Risnawati; Muhammad Tasjidin Teheni; La Jejen (Abdimas Universal, 2023)
One of the cases of micronutrient deficiency in Indonesia is iron anemia. Iron fortification can be done on baby porridge as Complementary Food for Breast Milk (MP-ASI) given to children aged 6 months to 24 months. production of free-range chicken, promoting the sale of free-range chicken online. In addition, knowledge transfer will be carried out to partners about processing chicken liver as fortification of iron in baby porridge in MPASI. The method used is pretest and posttest given to 20 participants to determine the extent of absorption given material. Evaluation of this activity will be carried out in a weekly period to monitor the indicators that have been set. The service was attended by 20 mothers of toddlers and cooperation partners, namely the owner of the "Mr. Desi Chicken Coop” which was carried out for approximately 5 weeks. The results of this service increase the knowledge of mothers of toddlers skills in making complementary foods (90%). This is carried out to provide provisions for partners and mothers of toddlers regarding the use of chicken liver as iron fortification in infant porridge in complementary foods, correct processing of chicken liver, sales promotion online to increase partners' earnings.